ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI PADI SAWAH DI DESA TUMANI KECAMATAN MAESAAN - Friska Erika Moonik; Rine Kaunang; Tommy Fredy Lolowang (Sam Ratulangi University, 2020)
This study aims to determine the effect of the use of land production factors, labor, seeds, urea and phonska fertilizers, as well as pesticides on the production of lowland rice farming in Tumani Village, Maesaan Sub-district. This research was conducted for two months from July to August 2019. The method of sampling used simple random sampling method. Data is collected by collecting primary data and secondary data. Primary data were obtained directly from 50 farmers as respondents through interviews with the help of a questionnaire while secondary data were obtained by searching documents from the Department of Agriculture. Analysis of the data used is the Cobb Douglas model regression analysis to see the effect of each production factor on the production produced. The results showed that, the variable area of land, seeds, phonska and labor had a significant effect, while the variable urea fertilizer and pesticides had no significant effect on the production of lowland rice in Tumani Village, Maustic District. * eprm *